2018
DOI: 10.1111/geb.12826
|View full text |Cite
|
Sign up to set email alerts
|

Winter temperature structures mangrove species distributions and assemblage composition in China

Abstract: Aim The identification of environmental variables associated with geographical range limits can shed light on the ecological and physiological constraints imposed by abiotic stresses. Mangrove forest is a coastal ecosystem restricted to the tropics and subtropics. However, the factors that influence fine‐scale assemblage composition of mangroves remain an open question. This study aimed to identify range‐limiting climate factor(s) associated with species composition that are likely to have influenced the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Low temperature has been regarded as one of the primary factors affecting the latitudinal range limits of mangrove species (Lugo and Patterson-Zucca, 1977;Duke et al, 1998;Stuart et al, 2007;Ross et al, 2009;Tomlinson, 2016;Osland et al, 2017;Wu et al, 2018). Yang and Lin (1998) showed an increase of cold resistance within K. obovata along latitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low temperature has been regarded as one of the primary factors affecting the latitudinal range limits of mangrove species (Lugo and Patterson-Zucca, 1977;Duke et al, 1998;Stuart et al, 2007;Ross et al, 2009;Tomlinson, 2016;Osland et al, 2017;Wu et al, 2018). Yang and Lin (1998) showed an increase of cold resistance within K. obovata along latitude.…”
Section: Discussionmentioning
confidence: 99%
“…Mangroves are temperature-sensitive plants, and thus low temperature may exert strong selective forces on natural populations. Temperature is likely a critical factor in determining mangrove community assemblage and species diversity (Yang and Lin, 1998;Wang et al, 2011;Ruan et al, 2013;Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the expansion of mangrove forests in subtropical and temperate regions is limited by its climate conditions, which in turn facilitate the invasion of freeze-tolerant salt marshes (Osland et al, 2017). Another possible explanation of this latitudinal pattern may be that the species richness of mangrove communities may decrease as the latitude rises, weakening the biotic resistance to invaders (Beaury et al, 2020;Guo et al, 2020;Wu et al, 2018).…”
Section: Latitudinal Trends In Mangroves and S Alternifloramentioning
confidence: 99%
“…Low air temperature is considered an important limiting factor for mangrove expansion into higher latitudes at a global scale (Chapman, 1975;Woodroffe and Grindrod, 1991;Quisthoudt et al, 2012;Osland et al, 2017b;Wu et al, 2018). This is explained since the temperature can directly and/or indirectly affect the physiological and phenological processes of the plants (Chuine and Beaubien, 2001;Larcher, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Predictions of mangrove range expansion can be improved since refined temperature thresholds for mangrove species frost damage, mortality, or recovery are somewhat better known nowadays (Quisthoudt et al, 2012;Cook-Patton et al, 2015;Osland et al, 2017b;Cavanaugh et al, 2018;Ximenes et al, 2018;Wu et al, 2018;Cavanaugh et al, 2019;Osland et al, 2020a,b;Devaney et al, 2020;Bardou et al, 2021;Chapman et al, 2021;Snyder et al, 2021). Moreover, Santos Borges et al (2019) showed that the germination rate of L. racemosa propagules is below 50% at air temperatures of 10 • C and 15 • C. Reduction in seedling stem elongation rate, altered leaf gas exchange rates, and increased mortality were associated with chilling events at 10 • C especially under high salinity and low humidity conditions (Devaney et al, 2020).…”
Section: Introductionmentioning
confidence: 99%